Reduced bone volumetric density and weak correlation between infection and bone markers in cystic fibrosis adult patients. Issue 9 (September 2016) - Gensburger, D.; Boutroy, S.; Chapurlat, R.; Nove-Josserand, R.; Roche, S.; Rabilloud, M.; Durieu, I.
Abstract Summary In our current adult CF population, low BMD prevalence was only 20 %, lower than that historically described. We found a mild increase of serum RANK-L levels, independent from the bone resorption level. The increased fracture risk in CF may be explained by a lower tibial cortical thickness and total vBMD. Introduction Bone disease is now well described in cystic fibrosis (CF) adult patients. CF bone disease is multifactorial but many studies suggested the crucial role of inflammation. The objectives of this study were, in a current adult CF population, to assess the prevalence of bone disease, to examine its relationship with infections and inflammation, and to characterize the bone microarchitecture using high resolution peripheral scanner (HR-pQCT). Methods Fifty-six patients (52 % men, 26 ± 7 years) were assessed in clinically stable period, during a respiratory infection, and finally 14 days after the end of antibiotic therapy. At each time points, we performed a clinical evaluation, lung function tests, and biochemical tests. Absorptiometry and dorso-lumbar radiographs were also performed. A subgroup of 40 CF patients (63 % men, 29 ± 6 years) underwent bone microarchitecture assessment and was age- and gender-matched with 80 healthy controls. Results Among the 56 CF patients, the prevalence of low areal BMD (T-score < −2 at any site), was 20 % (95 % CI: [10.2 %; 32.4 %]). After infections, serum RANK-L (+24 %, p = 0.08) and OPG (+13 %, p = 0.04) were increased with a stable ratio. Microarchitectural differences were mostly observed at the distal tibia, with lower total and cortical vBMD and trabecular thickness (respectively −9.9, −3.0, and −5 %, p < 0.05) in CF patients compared to controls, after adjustment for age, gender, weight, and height. Conclusions In this study, bone disease among adult CF patients was less severe than that previously described with only 20 % of CF patients with low BMD. We found a mild increase of biological marker levels and an impaired volumetric density of the tibia that may explain the increased fracture risk in CF population.